Fact and fiction : literary and scientific cultures in Germany and Britain - Lehleiter, Christine (2016)
"Fact and Fiction explores the intersection between literature and the sciences, focusing on German and British culture between the eighteenth century and today. Observing that it was in the eighteenth century that the divide between science and literature as disciplines first began to be defined, the contributors to this collection probe how authors from that time onwards have assessed and affected the relationship between literary and scientific cultures"–...